2014
DOI: 10.1587/transele.e97.c.132
|View full text |Cite
|
Sign up to set email alerts
|

Nb 9-Layer Fabrication Process for Superconducting Large-Scale SFQ Circuits and Its Process Evaluation

Abstract: SUMMARYWe describe the recent progress on a Nb nine-layer fabrication process for large-scale single flux quantum (SFQ) circuits. A device fabricated in this process is composed of an active layer including Josephson junctions (JJ) at the top, passive transmission line (PTL) layers in the middle, and a DC power layer at the bottom. We describe the process conditions and the fabrication equipment. We use both diagnostic chips and shift register (SR) chips to improve the fabrication process. The diagnostic chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 17 publications
(31 reference statements)
0
58
1
Order By: Relevance
“…Also, by virtue of recent developments in fabrication technology with a multi-layered structure [13], [14] and some energy-efficient circuit technology [15]- [19], several research projects on SFQ microprocessors have been undertaken [20], [21], and an 8-bit microprocessor composed of more than 10,000 Josephson junctions successfully operates at 50 GHz [7]. In addition, inventions of several novel superconductor devices based on new physical phenomena have made the SFQ logic technology much more attractive, e.g., superconductor junctions with one or more ferromagnet layers show different electrical characteristics depending on the magnetic states, by which we can obtain high-density, low-power, cryogenic memory compatible with SFQ circuits [22], [23].…”
Section: Sfq Circuitsmentioning
confidence: 99%
“…Also, by virtue of recent developments in fabrication technology with a multi-layered structure [13], [14] and some energy-efficient circuit technology [15]- [19], several research projects on SFQ microprocessors have been undertaken [20], [21], and an 8-bit microprocessor composed of more than 10,000 Josephson junctions successfully operates at 50 GHz [7]. In addition, inventions of several novel superconductor devices based on new physical phenomena have made the SFQ logic technology much more attractive, e.g., superconductor junctions with one or more ferromagnet layers show different electrical characteristics depending on the magnetic states, by which we can obtain high-density, low-power, cryogenic memory compatible with SFQ circuits [22], [23].…”
Section: Sfq Circuitsmentioning
confidence: 99%
“…Our DC SQUID sensor consists of two JJs, which were designed to have a junction area of each JJ of 2.2 m x 2.2 m and the critical current Ic of 12.5 A. It was reported that the typical variation in JJ critical currents is better than 2% [20]. In each single sensor, the pick-up coil is connected to a SQUID washer directly, which was covered fully by superconducting Nb film.…”
Section: Design To Fabricate Squid Sensormentioning
confidence: 99%
“…InductEx remains the only simulator other than Lmeter [5] that can handle full-gate superconductive circuit extractions. We discuss the background to 3D inductance extraction, and show how extraction models are constructed and used to find inductances, coupling and current distribution for circuit layouts in the AIST advanced process (ADP2) [13], [14] and standard process (STP2). We also discuss developments and refinements that were necessary to model ADP2 and STP2 layouts.…”
Section: Introductionmentioning
confidence: 99%